Armstrong's Handbook of Management and Leadership A Guide to Managing for Results. - Armstrong, Michael, 1928- (London : Kogan Page, 2009)
Providing guidance on the processes of management and leadership, this work presents particular reference to what managers and aspiring managers need to know about the skills of management and approaches to effective leadership.
Previous ed.: published as A handbook of management and leadership by Michael Armstrong and Tina Stevens. 2005.
Includes bibliographical references and index.
Keywords: Management; Leadership; Business and Management